2018
DOI: 10.1016/j.clcc.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Tools to Support Decision-making for Palliative Treatment of Metastatic Colorectal Cancer: A Systematic Review

Abstract: A limited number of DSSs are available to support palliative treatment decisions for patients with mCRC, and the evidence regarding their discriminatory ability and calibration is too limited to recommend their use. New DSSs comparing multiple treatment options and presenting both treatment benefits and harms are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Moreover, low to moderate correlations observed among the HRQoL domains (Spearman's rho: 0.3-0.5; data not shown) indicated that the low HRQoL groups for the separate domains were not comprised of the same CRC survivors, reflecting that HRQoL is a multi-dimensional construct consisting of different aspects that are covered by the separate domains. Footnotes: a Twelve candidate predictors were forced into each model, as there was strong evidence for their association with HRQoL in a systematic review [19] b Candidate predictors for which moderate or weak evidence was found, were selected with backwards selection procedures using Akaike's Information Criterion (p < 0.1573). The following candidate predictors were not included in any of the models: tumor localization, marital status, fruit and vegetable consumption, alcohol consumption and waist circumference c Regression coefficients display the ln (odds) change in outcome, but no standard errors could be calculated after shrinkage; Formula for the probability of having low HRQoL = 1 / (1 + exp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, low to moderate correlations observed among the HRQoL domains (Spearman's rho: 0.3-0.5; data not shown) indicated that the low HRQoL groups for the separate domains were not comprised of the same CRC survivors, reflecting that HRQoL is a multi-dimensional construct consisting of different aspects that are covered by the separate domains. Footnotes: a Twelve candidate predictors were forced into each model, as there was strong evidence for their association with HRQoL in a systematic review [19] b Candidate predictors for which moderate or weak evidence was found, were selected with backwards selection procedures using Akaike's Information Criterion (p < 0.1573). The following candidate predictors were not included in any of the models: tumor localization, marital status, fruit and vegetable consumption, alcohol consumption and waist circumference c Regression coefficients display the ln (odds) change in outcome, but no standard errors could be calculated after shrinkage; Formula for the probability of having low HRQoL = 1 / (1 + exp.…”
Section: Discussionmentioning
confidence: 99%
“…This final and important step of prediction research is often overlooked. For instance, several prediction models have been developed, and to a lesser extent externally validated, for estimating probabilities of survival in CRC patients to be used when considering different treatment options [18][19][20]. One recently published prediction model for survival has even presented an online tool for use in clinical practice during the treatment phase [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognostication systems have been developed to assist oncologists and spinal surgeons in evaluating treatment options, their benefits (likelihood of improving neurological function, decreasing pain and restoring spine stability) and their disadvantages (surgical morbidity, mortality and recovery time) (7,10). Ideally, a prognostication system would compare different management options, evaluate the outcome of surgical intervention based on survival, toxicity and cost-effectiveness, and propose a more rational, objective, safe and reproducible management (3,7,10). The Tokuhashi scoring system was introduced in 1989 as a 'scoring system for the preoperative evaluation of a patient's prognosis with a metastatic spinal tumor' (11) and it was revised in 2005 (7).…”
Section: Prognostication Systemsmentioning
confidence: 99%
“…Colorectal cancer is the fourth cause of cancer-related death worldwide [1]. The 5-year survival rate of metastatic colorectal cancer remains at a disappointing 10-20% despite significant improvements in metastatic colorectal cancer management via targeted therapies in combination with chemotherapy [2,3]. In the past two decades, many molecular markers and clinicopathological factors of colorectal cancer have been suggested as predictors of the postoperative prognosis of colorectal cancer patients to help clinicians determine appropriate treatments [4].…”
Section: Introductionmentioning
confidence: 99%